The study characteristics of electrospinning nanofibers in polyetyhlene oxide(PEO)for controlled released and target delivery - Ismail Ammar, Mohamat (2013)
Nanofibers that develop by using electrospinning technique are a common study field nowadays.There are few advantages of using this technique in producing nanofibers such as in drug delivery and controlled released system, pharmaceuticals products,biotechnological purposes and etc. By using this technique in producing nanofibers, ethanol was chosen to be the solvent instead of water in producing nanofibers.The type of solvent and polymer are believe affecting the morphological structure of the nanofibers and thus the drug delivery system.The configuration of the electrospinning was kept constant in every test run and only the solvent concentration and molecular weight of the polymer were manipulated.This is to check in what conditions will the nanofibers having the best morphology,tensile strength and distribution of fibers.Ethanol is very suitable in producing good nanofibers.However the percentage concentration of ethanol should be check in order to avoid the protein embedded in the nanofibers denature.Stable protein is selected to be used in the nanofibers in avoiding deformation of drugs if to be used commercially.